Cell Delivery: Core–Shell Hydrogel Microcapsules for Improved Islets Encapsulation (Adv. Healthcare Mater. 5/2013). Issue 5 (2nd May 2013) - Ma, Minglin; Chiu, Alan; Sahay, Gaurav; Doloff, Joshua C.; Dholakia, Nimit; Thakrar, Raj; Cohen, Joshua; Vegas, Arturo; Chen, Delai; Bratlie, Kaitlin M.; Dang, Tram; York, Roger L.; et al.
<x xml:space="preserve">Abstract</x> Islets encapsulation is a promising approach for the treatment of Type I diabetes. On page 667, Daniel G. Anderson and co‐workers report a novel design of microcapsules with core–shell structures using two‐fluid co‐axial electro‐jetting. Improved encapsulation and diabetes correction is achieved in a single step by simply confining the islets in the core region of the capsules. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>